18F FDG PET-CT in Predicting Acute Respiratory Distress Syndrome: A Case Report - Ahsan, Mostofa Shamim; Begum, Shamim MF; Mutsuddy, Pupree; Mandal, Tapati; Salekin, Simoon (Bangladesh Journal of Nuclear Medicine, 2018)
Abstract not available Bangladesh J. Nuclear Med. 21(1): 46-47, January 2018